Activity size distribution of radioactive nuclide 7Be at different locations and under different meteorological conditions. (1st September 2019) - Ioannidou, A.; Eleftheriadis, K.; Gini, M.; Gini, L.; Manenti, S.; Groppi, F.
Abstract: The activity size distributions of the natural radionuclide tracer 7 Be in different size fractions (<0.4 μm, 0.4–0.7 μm, 0.7–1.1 μm, 1.1–2.1 μm, 2.1–3.1 μm, 3.1–4.2 μm, 4.2–5.8 μm, 5.8–9.0 μm > 9.0 μm) were determined at four different site places in Northern Italy during the four seasons of the year 2011. One cascade impactor operated at the LASA-station considered the reference station and the other used for simultaneous measurements at the three other sites. Three sets of independent samples were collected during every season of the year 2011. The initial activity distribution inverted into smooth size distribution. The model parameters successfully defined to obtain the best fit-curve and two or three modes were resolved, with the predominant fit at the accumulation range. The lowest Activity Median Aerodynamic Diameter (AMAD) values were observed during summer. The AMAD values were anticorrelated with 7 Be activities, while they were correlated with Relative Humidity. Similar AMAD values in suburban and urban regions were observed during all periods of the year. AMAD values of 7 Be aerosol particles in areas with poor air quality were greater than those at the less polluted environments far from anthropogenic activities regions. This indicates that 7 Be AMAD values could be used as an index of air quality conditions in areas like the Po Valley. Highlights: For first time 7 Be AMAD obtained by simultaneous measurements at different areas. The 7 Be AMAD values were anticorrelated with 7 Be activities. At all stations the 7 Be concentrations are lower during winter and higher at summer. The greatest 7 Be AMAD values observed at the most polluted areas throughout the year. Two or three modes revealed by inverting the initial activity distribution to smooth.